Identification of differentially expressed circular RNAs in keloid and normal skin tissue by high‐throughput sequencing. Issue 2 (17th January 2021) - Zhang, Jing; Liu, Ninghua; Wu, Xiufa; Wu, Peixuan; Song, Nan; Ma, Jing
Abstract: Keloid is a kind of pathological skin scar with unclear molecular pathology. Circular RNAs (circRNAs) are involved in the occurrence and development of many diseases; however, their relationship with keloid is not well understood. To investigate the involvement of dysregulated circRNAs in keloid. Thirty‐seven keloids and 37 normal skin tissues were collected, and the changes of circRNAs, microRNAs (miRNAs) and mRNAs in 3 keloids and 3 normal samples by high‐throughput sequencing were detected first. Based on the circRNA‐miRNA‐mRNA interaction network construction, gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis combining several signaling pathways associated with keloid formation and progression, the circRNAs required further verification were screened out. The expression levels of the selected circRNAs were verified in 37 keloids and 37 normal skin tissues using quantitative real‐time polymerase chain reaction (QPCR). The interaction of candidate circRNA and its predicted binding miRNA was tested by dual‐luciferase reporter gene experiment. Compared with normal controls, there was an average of 120 and 12 circRNAs, 44 and 63 miRNAs, 656 and 156 mRNAs were upregulated and downregulated, respectively, in keloids. According to the analysis of bioinformation, six circRNAs were picked out. The QPCR validation results of two upregulated circRNAs (hsa_circ_0001320 and circCOL5A1) were consistent with previous sequencing results. The interaction between hsa_circ_0001320 and miR‐574‐5p was confirmed. This study makes it clear that the abnormal expression of circRNAs may be related to the pathological process of keloid.